Indigenous Futurity in the Living Root Bridges of the Khasi-Jaiñtia Hills of India: A Documentary Essay - Randolph V. Langstieh (eTropic: electronic journal of studies in the tropics)
The Living Root Bridges found in the southern valleys of the Khasi-Jaiñtia Hills of Meghalaya, India, attract tourists from all over the world to admire nature’s extravagance. Apart from the attraction of these natural entities, the underlying values and principles that nature has to offer lays out a comprehensive understanding of an Indigenous futurism in the mountainous landscape of this wet tropical region. This paper is based on the documentary film Ki Thied Ka Lawei (Roots of Sustainability), directed by the author. The documentary depicts the ongoing practice of constructing and reconstructing a bamboo bridge in the village of Shiliang Jashar yearly since 1988. The bamboo bridge is used by locals to commute over the Wah Jashar river, and simultaneously acts as a scaffold for the formation of a living root bridge into the future. Another semi-formed root bridge in a neighbouring village of Mawkyrnot, gives a clear insight into the growth of these root bridge formations. This essay exhibits stills from the documentary and describes and analyses the ensuing bridge-making, rooted in Indigenous knowledge systems of nature-culture relationality passed on by the Khasi ancestors in an act of Indigenous futurity.